EFIKASI CENDAWAN ENTOMOPATOGEN LECANICILLIUM LECANII TERHADAP BEMISIA TABACI (HEMIPTERA: ALEYRODIDAE) PADA KEDELAI - Yusmani Prayogo . (Universitas Lampung, 2014)
Efficacy of entomopathogenic fungi Lecanicillium lecanii to Bemisia tabaci (Hemiptera: Aleyrodidae) on Soybean. Bemisia tabaci is one of the most important pests on soybean, because in addition to direct damage also as vectors of viruses and stimulated the growth of sooty mold. The efficacy of entomopathogenic fungi Lecanicillium lecanii to control B. tabaci carried out at Muneng field research station of Probolinggo in June until September 2012. Research using a split plot design, the main plot is two soybean varieties, namely Argomulyo and Wilis. Subplot is the time application of fungi L. lecanii with conidia densities of 107 and 109/ml. The results showed that Argomulyo more preferred by B. tabaci compared Wilis variety. Nine times application of L. lecanii using 107/ml conidia densities were applied every week the started on 14-70 days after planting (DAP) was able to suppress of B. tabaci in the field. However, planting Wilis varieties with nine times application of L. lecanii using conidia densities 109/ml were recommended. Controlling of B. tabaci on Argomulyo variety use L. lecanii or lamda sihalotrin showed no significantly due to the result seed weight is lower than compare with Wilis untreated. Application of L. lecanii use with the highest conidia densities (109/ml), no negative effect to the survival on survival of various predators; i.e. Coccinella sp., Oxyopes sp. and Paederus sp. Therefore, L. lecanii most likely to be used as an effective biopesticide agent to control of B. tabaci and as substitute to chemical insecticides.